Looking towards the United Nations Conference on Environment and Development 1992 : national preparations and positions : the case of Barbados. - Griffith, Mark (1992)
Presents the main elements of Barbados' preparatory process for UNCED, strategies for sustainable development and the country's position on some key issues to be addressed by UNCED.